2019
DOI: 10.1139/facets-2019-0002
|View full text |Cite
|
Sign up to set email alerts
|

Perspective-based search: a new paradigm for bursting the information bubble

Abstract: Nowadays, individuals heavily rely on search engines for seeking information. The presence of information bubbles (filter bubbles and echo chambers) can threaten the effectiveness of these systems in providing unbiased information and damage healthy civic discourse and open-minded deliberation. In this paper, we propose a new paradigm for search that aims at mitigating the information bubble in the search. The paradigm, which we call perspective-based search (PBS), is based on the intuition that in a fair sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Finally, research using both theoretical and real-life social networks clearly showed that the structure of the network itself as well as the algorithm responsible for selecting the information displayed to the users have an important role in the progressive isolation of communities online (Bakshy et al, 2015; Epstein and Robertson, 2015; Lazer, 2015), although individuals themselves also tend to deliberately limit their exposure to ideologically adverse content (Bakshy et al, 2015). Recent results suggest that diversifying the sources of information users are exposed to rather than tailoring them to their preferences may help combat community isolation and the formation of opinion bubbles (Tabrizi and Shakery, 2019).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Finally, research using both theoretical and real-life social networks clearly showed that the structure of the network itself as well as the algorithm responsible for selecting the information displayed to the users have an important role in the progressive isolation of communities online (Bakshy et al, 2015; Epstein and Robertson, 2015; Lazer, 2015), although individuals themselves also tend to deliberately limit their exposure to ideologically adverse content (Bakshy et al, 2015). Recent results suggest that diversifying the sources of information users are exposed to rather than tailoring them to their preferences may help combat community isolation and the formation of opinion bubbles (Tabrizi and Shakery, 2019).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…To address this challenge, Tabrizi & Shakery (2019) recently proposed a multi‐perspective search paradigm that enables the bursting of the filter bubble. According to this paradigm, users are made aware of the bubble problem, informed about the existence of different perspectives on the topic, and provided with tools to control which perspective to view the results from.…”
Section: Introductionmentioning
confidence: 99%
“…The authors argue that the proposed solution increases the system's transparency and trust and can prevent individuals from moving to extremes, promote critical thinking, and prevent belief in falsehoods. Other solutions presented in the literature, such as avoiding personalization, intentionally exposing users to less popular content, diverse topics, and serendipity (Amrollahi, 2021; Tabrizi & Shakery, 2019; Geffet & Feitelson, 2001), seem to be less effective, as many users may be frustrated by receiving irrelevant content with no ability to control their information preferences (Tabrizi & Shakery, 2019; Munson & Resnick, 2010). However, the authors left the implementation of the proposed paradigm to future research (Tabrizi & Shakery, 2019).…”
Section: Introductionmentioning
confidence: 99%